Evaluating high-intensity interval-training validity using critical power in rowing - Dicks, N. D.; Phuaklee, P.; Ketterling, J. J.; Pettitt, R. W. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study evaluated the effectiveness of the 3-minute all-out test (3MT) in rowing for determining critical power (CP) and work capacity above CP (W') to prescribe high-intensity interval training.